THE FACTORS OF RELATED TO NURSING JOB SATISFACTION IN THE INPATIENT AT HARAPAN BUNDA BATAM HOSPITAL 2015 - asfri sri rahmadeni (Universitas Fort De Kock, 2020)
Job satisfaction is a pleasant mental state perceived by a person on the job because of the requirement for adequately. Someone who has a high level of job satisfaction will have a positive feeling about the job. This study aims to look at the factors associated with job satisfaction of nurses in the hospital harapan bunda batam 2015. The design of this study using cross sectional study design. Samples taken by total sampling with total sample of 74 nurses. Results of the study are the factors mitivator and hygiene factors more than half are not implemented. Statistical test results obtained Motivator factors that have a relationship with the achievement of satisfaction of nurses are working nurse with p = 0.020, recognition of the work with p = 0.003, and the work itself with p = 0.027. Hygiene factors linked to the satisfaction of nurses are working regulations with p = 0.013, p = 0.011 salary, and interpersonal relationships with p = 0.070. After multivariate analysis obtained factor most dominant working conditions and job satisfaction of nurses with OR = 5.123. The implications of this study demonstrated that the mother's hospital hopes more attention to factors related to job satisfaction of nurses so that the quality of service provided nurses can work well